Comparison of Mean Upper Lip Length in Individuals with Competent Lips, Lips Apart and Incompetent Lips - Madiha Rasheed, Batool Sajjad, Asha Devi, Waheed Gul Shaikh, Humaira Naureen, Marium Azfar (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The human lips are the essential structure for speech, facial expression and oral functions like eating, drinking and breathing. The orthodontic treatment is very crucial for the advancement of the facial expression Lip incompetence is a condition in which the lips fail to close adequately leading to negative effects on speech, facial esthetics and oral functions. Study design: It is a retrospective study conducted at WATIM Dental College Rawat, Rawalpindi and Altamash Institute of Dental Medicine, Karachi for the duration of six months from Jan 2022 to June 2022. Material and Methods: The patients were divided into three groups. The patients that did not follow the inclusion criteria were excluded from the study. Group I had patients with competent lips, group II had patients with their lips apart and group III had incompetent lips. There were 45 patients in each group. Results: The length of group I members was 19.8 mm for men and 18.7 mm for women, which was less than group III individuals with 20 mm and 18.9 mm average upper lip length for males and females. Group II patients had a length of 17.5mm for male patients and 16.4 mm for female patients. The P-value was calculated and the results were statistically significant. Conclusion: The length of group I members was 19.8 mm for men and 18.7 mm for women, which was less than group III individuals with 20 mm and 18.9 mm average upper lip length for males and females. Group II patients had a length of 17.5mm for male patients and 16.4 mm for female patients. Keywords: Lip incompetence and competent lips.